Trichomonas vaginalis and growing concern over drug resistance: a systematic review. (26th July 2021) - Marques‐Silva, M.; Lisboa, C.; Gomes, N.; Rodrigues, A.G.
Abstract: In the late 90s, a sharp increase of treatment failures of Trichomonas vaginalis (TV) infections with metronidazole (MTZ) was reported, representing a problem due to limited treatment options. We proposed to review the available evidence on the frequency of MTZ resistance by TV isolates and the relationship between treatment failure and in vitro resistance to MTZ. A systematic review based on the PRISMA guidelines was conducted by searching published studies in three different databases (PubMed, Scopus and Web of Science) up to December 2020. The extracted studies were uploaded to Covidence software; screening was guided based on inclusion and exclusion criteria. Additionally, different articles were included through other sources. For each article, study design, objectives, study population and key outcomes were summarized. We found 403 references from the databases and four extra studies. After duplicate removal and screening of title, abstract and full text, 27 studies were included. The selected studies were published between 1983 and 2019; all except one addressed only vaginal TV infection. We identified four major populations in vitro MTZ resistance: two studies evaluated female adolescents; other two assessed HIV‐positive women. Fifteen studies considered MTZ resistance in newly diagnosed vaginal TV infection. Finally, eight articles studied in vitro susceptibility of isolates from women with clinical resistant trichomoniasis. High level of in vitro MTZ resistance was rare; low‐moderate level was described in most of the cases. Although clinical resistance to MTZ of trichomoniasis was widely reported, there was a paucity of prospective controlled studies. Our review unveiled the need to standardize susceptibility testing, to define breakpoints for detection of MTZ‐resistant isolates and to correlate with clinical outcome. It is important to establish criteria to define clinical resistance to MTZ. Such a consensus would foster the development of surveillance studies about clinical and microbiological response to MTZ treatment.